2022
DOI: 10.1186/s10194-022-01478-w
|View full text |Cite
|
Sign up to set email alerts
|

Disease- and headache-specific microRNA signatures and their predicted mRNA targets in peripheral blood mononuclear cells in migraineurs: role of inflammatory signalling and oxidative stress

Abstract: Background Migraine is a primary headache with genetic susceptibility, but the pathophysiological mechanisms are poorly understood, and it remains an unmet medical need. Earlier we demonstrated significant differences in the transcriptome of migraineurs' PBMCs (peripheral blood mononuclear cells), suggesting the role of neuroinflammation and mitochondrial dysfunctions. Post-transcriptional gene expression is regulated by miRNA (microRNA), a group of short non-coding RNAs that are emerging bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 122 publications
0
11
0
Order By: Relevance
“…Several authors have made an effort in previous studies to identify potential miRNAs as peripheral biomarkers of migraine [12]. Numerous miRNAs have been described associated with pain-free patients with migraine in comparison to healthy controls: miR-382-5p (overexpressed in serum and PBMC) [21,23]; miR-34a-5p (over-expressed in serum, saliva and PBMC) [21,24]; miR-27b (over-expressed in plasma) [25]; miR-181a, let-7b, and miR-22 (under-expressed in PBMC) [25]; miR-155, miR-126, and let-7 g (over-expressed in plasma) [18]; miR-30 (over-expressed in PBMC) [69]; miR-5189-3p, miR-3613-5p, miR-99a-3p, miR-542-3p (over-expressed in PBMC) and miR-96-5p (under-expressed) [26]. Results are heterogenous and study-dependent but not only because there are differences in lab procedures, biological matrix or sample size but mainly because of the large degree of heterogeneity between study groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have made an effort in previous studies to identify potential miRNAs as peripheral biomarkers of migraine [12]. Numerous miRNAs have been described associated with pain-free patients with migraine in comparison to healthy controls: miR-382-5p (overexpressed in serum and PBMC) [21,23]; miR-34a-5p (over-expressed in serum, saliva and PBMC) [21,24]; miR-27b (over-expressed in plasma) [25]; miR-181a, let-7b, and miR-22 (under-expressed in PBMC) [25]; miR-155, miR-126, and let-7 g (over-expressed in plasma) [18]; miR-30 (over-expressed in PBMC) [69]; miR-5189-3p, miR-3613-5p, miR-99a-3p, miR-542-3p (over-expressed in PBMC) and miR-96-5p (under-expressed) [26]. Results are heterogenous and study-dependent but not only because there are differences in lab procedures, biological matrix or sample size but mainly because of the large degree of heterogeneity between study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several pilot studies have described miRNAs as potential peripheral biomarkers of migraine disease [18][19][20][21][22][23][24][25][26]. Nevertheless, studies are scarcely comparable and reproducible not only because of the lack of standardized protocols, biological matrix or sample size but mainly because of the heterogeneous population and clinical variability included.…”
Section: Introductionmentioning
confidence: 99%
“…Among the molecules currently under investigation, miRNAs have significant potential. 45 Migraine-specific miRNAs have been discovered in miRNA analyzes of peripheral blood monocytes of migraine patients. In our study, miR-3158-5p has potential as one of the migraine diagnosis candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the active complex interacts with the 3′-UTR of target mRNA through complementary pairing of base pairings, causing translational repression or RNA degradation (Figure 1A). 83−85 Through this process, miRNAs were involved in a series of cellular processes, including apoptosis, 4−6 oxidative stress, 7 cell proliferation, 8,9 inflammation, 10,11 hematopoiesis, 4,12 and tumorigenesis. 13,14 Recent studies revealed that miRNAs not only have an intracellular function but also stably exist in biological fluids such as saliva, cerebrospinal fluid, plasma, serum, gingival fluid, and urine.…”
Section: Micrornasmentioning
confidence: 99%
“…A particular miRNA can target various mRNAs to induce translational repression or RNA degradation, and one mRNA can be regulated by multiple different miRNAs . By modulating gene expression at the post-translational level, miRNAs play a critical role in a series of cellular processes, including apoptosis, oxidative stress, cell proliferation, , inflammation, , hematopoiesis, , and tumorigenesis. , Importantly, miRNAs not only have an intracellular function but also stably exist in biological fluids such as saliva, cerebrospinal fluid, plasma, serum, gingival fluid, and urine. Therefore, circulating miRNAs are considered biomarkers of disease and can regulate gene expression in distal cells or organs. ,, …”
Section: Introductionmentioning
confidence: 99%